EFL Students’ Attitude toward Learning the English language based on Teacher’s Gender: A Case study in Cambodia Context - Kimleang, Meng; Arsyad, Safnil (UNIB Press, 2022)
Gender is defined as all of the social and cultural habits, roles, conditions, and responsibilities regardless of one's biological gender, that are necessary for a society. This study aims to explore EFL students' attitudes toward learning the English Language base on teachers' gender. When teachers assess pupils with high levels of problem conduct for special education referral, cross break analysis finds that male teachers are substantially more likely than female teachers to decide not to recommend. The impact of teacher gender on this scenario has been investigated, but the results have been equivocal. Furthermore, while teacher expectations have influenced student academic achievements and student gender stereotypes have molded such expectations, the gender of the teacher has been overlooked in this context. The descriptive quality method was used in this research with the students from the National University of Battambang who currently studying for master's degrees. The questionnaires were given along with the individual interviews. The result showed that female teachers were the most selected due to the attitude of the students when they were studying with female teachers. Keywords: Behavioral Aspect of Attitude, Cognitive Aspect of Attitude, Emotional Aspect of Attitude, Teacher gender.